The importance of social capital in participatory ecological restoration projects - Ceccon, Eliane (2024)
Social capital is a theoretical construct that proposes scenarios where values such as cooperation, communication, and trust between people can create an ideal environment for solving socio-environmental problems. Ecological restoration is gaining momentum, since 2021-2030 is currently the “Decade of United Nations about Ecosystem Restoration”. However, several authors consider that ecological restoration, in addition to repairing an ecosystem, should aim to generate collective actions, social learning, new human values, and new political relationships with nature. The objective of this study is to evaluate the importance of the social capital in the permanence of two participatory restoration projects, in two marginalized traditional indigenous communities in Mexico, through the case study and participant observation methodology. Clear evidence was found that differences in the levels of social capital between the two communities affected the permanence of the two projects.